2013
DOI: 10.1159/000351182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Times Weekly Eight-Hour Nocturnal Hemodialysis on Volume and Nutritional Status

Abstract: Background: This prospective cohort study compared the changes in body water composition and nutritional parameters measured with multifrequency bioimpedance analysis between 8-hour three times weekly nocturnal hemodialysis (NHD) and 4-hour conventional hemodialysis (CHD) patients. Patients and Methods: 55 patients on CHD and 57 patients on NHD were included in the study. Multifrequency bioimpedance analysis was performed at baseline and at the 12th month. The primary outcomes of the study were changes in extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…Most studies have found that phosphate removal is better with long-duration nocturnal haemodialysis than with conventional treatment and that there is a lower use of phosphate binders [5,6,16,20,21,22]. In our study, better phosphate control was also observed with a reduced need for phosphate binders from 84% to total withdrawal.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Most studies have found that phosphate removal is better with long-duration nocturnal haemodialysis than with conventional treatment and that there is a lower use of phosphate binders [5,6,16,20,21,22]. In our study, better phosphate control was also observed with a reduced need for phosphate binders from 84% to total withdrawal.…”
Section: Discussionsupporting
confidence: 72%
“…Since then, the contribution of dialysis duration has been under debate. However, similar experiences were published only after 2009 from Canada [5,16], the United Kingdom [17,18], the United States [19], Germany [6], Turkey [20,21], and Slovenia [22]. An every-other-day haemodialysis scheme has been used by the Lecce group since 1972 to avoid long weekend periods [10], but no other experiences have been reported, even though the long weekend interval is known to increase the risk of mortality [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutritional parameters have been examined in a number of studies on intensified HD, both in-center and at home, but the data are inconsistent [20]. Most recently, the effect of thrice weekly, nocturnal hemodialysis on nutrition was examined in 55 conventional and 57 nocturnal patients [21]. After 12 months of prescribed treatment, patients on nocturnal HD had significantly improved serum albumin compared to conventional HD patients.…”
Section: Dialysis Adequacymentioning
confidence: 99%